Conceptual Framework for IFRS Adoption, Audit Quality and Earnings Management: The Case of Bangladesh - Mohammad Tariq Hasan; Azhar Abdul Rahman (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
This study propose to explore the moderating role of audit quality on the relationship between IFRS adoption and earnings management as well as the effect of IFRS adoption on earnings management in the context of Bangladesh, as developing economy. Earlier literature document that the relationship among IFRS adoption, audit quality and earnings management are not conclusive. In case of IFRS adoption, it is incoherent which may be the result of difference in culture, practices and legal strength of the country. This study considers discretionary accruals as proxy of earnings management which is measured by the extended modified Jones model. Moreover, the influence of audit quality on the association between IFRS adoption and earnings management is also proposed to investigate. This study expects to explore the effect of IFRS adoption on earnings management in the context of developing country, like Bangladesh. It may be informative for the reader to understand the outcome of IFRS adoption, audit quality on earnings management in developing economy.